The Relationship Between Students’ Self-Perception as EFL Learners and Their Motivation to Learn English - Musyarrafah, Musyarrafah; Abdul Haris Sunubi; Zulfah Fakhruddin; Magdahalena Tjalla; Mujahidah (Institut Agama Islam Negeri Parepare, 2025)
Background: English language proficiency is essential in today’s globalized world, yet students in many developing countries, including Indonesia, exhibit varying levels of language proficiency. This study investigates the relationship between students’ self-perception as language learners and their motivation to learn English, focusing on how learners' beliefs about their abilities affect their engagement in learning activities. Research Objectives: The primary objective of this research is to examine the correlation between students' self-perception and their motivation to learn English. Specifically, it seeks to determine whether students who perceive themselves positively as language learners are more motivated to engage in English learning activities. Methods: A quantitative correlational design was employed, using a survey with two validated instruments: the Beliefs About Language Learning Inventory (BALLI) to measure self-perception, and the Attitude/Motivation Test Battery (AMTB) to assess motivation. The study involved 21 secondary school students from a rural Islamic school in Indonesia. Descriptive statistics, normality tests, and Pearson’s product-moment correlation were used for data analysis. Results: The results revealed a positive but statistically non-significant correlation between self-perception and motivation (r = 0.343, p = 0.128). Students demonstrated moderate self-perception and relatively high motivation levels, with motivation being slightly higher than self-perception. Despite a positive trend, the correlation did not reach statistical significance, suggesting that factors beyond self-perception influence motivation. Conclusions: Although the correlation was not significant, the results suggest that students who perceive themselves positively tend to report higher motivation. These findings imply that fostering learners’ confidence and beliefs in their language ability may be beneficial. Further research with larger and more diverse samples is recommended to validate these results and explore mediating factors.